ARAS Method for Ranking Vocational High School Students - Achmad Andrian Maulana; Muhammad Muharrom Al Haromainy; Afina Lina Nurlaili (Komunitas Dosen Indonesia, 2025)
Student performance assessment is a crucial component in strengthening the quality of vocational education. At SMK Muhammadiyah 2 Jogoroto, Kab. Jombang, the evaluation process is still conducted manually and relies primarily on report card scores, leading to subjectivity, inconsistency, and a limited representation of students’ competencies. This study develops a Decision Support System (DSS) by integrating the Rank Order Centroid (ROC) weighting technique and the Additive Ratio Assessment (ARAS) method to provide a clearer and more systematic multicriteria evaluation framework. The analysis involves ten student alternatives evaluated using six criteria: average report card score, attitude, absenteeism, extracurricular activities, achievements, and industrial internship performance. ROC is applied to generate proportional criterion weights based on ranked priority, while ARAS is used to execute the core computational stages, including normalization of each criterion, application of weighted values, calculation of the optimal function score (Si), and determination of utility values (Ui) to rank student performance. The results indicate that the system yields consistent outcomes, with Nikmatuz achieving the highest utility value of 2.65224526 and identified as the top-performing student. These findings show that combining ROC and ARAS enhances assessment accuracy, reduces evaluator bias, and improves transparency in the ranking process. Beyond this case study, the proposed model demonstrates potential for broader application in vocational institutions seeking structured, data-driven mechanisms to evaluate academic and non-academic competencies more comprehensively.